Being consequential about restorative justice - Walgrave, Lode (Studies in Restorative Justice, 2021)
In this anthology, Professor Emeritus Lode Walgrave, a pioneer in the field of juvenile justice and restorative justice, revisits a selection of his publications, going back to the late 1990s to the late 2010s, on restorative justice as a response to offending. These include reflections on why restorative justice is valuable as well as on how it can and should be implemented. Can reparation be imposed and how would that relate to retribution? Is there room for punishment? The broader field is explored by examining how restorative justice contributes to civilising criminal justice and to a ?criminology of trust?, all based on his socio-ethical concept of ?common self-interest?. In newly written introductory and concluding chapters, Walgrave explains how this journey in writing resulted in developing a consequential approach to restorative justice, which prioritises restorative responses to crime and delinquency